1996
DOI: 10.1111/j.1399-6576.1996.tb04553.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of desflurane on systemic, preportal and renal circulatory responses to infra‐renal aortic cross‐clamping in the pig

Abstract: DES effectively controlled increases in proximal blood pressure during AXC. The increases in RREN and RPORT that were seen during AXC at control were inhibited by 9.8% DES. Consequently, at this DES dose, both QREN and QPORT increased during AXC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Even so, with isoflurane in an intermediate concentration to those used by previous authors, there has been during aortic cross-clamping the same MBP behavior observed in the group receiving 0.7% isoflurane, that is, there was no impediment for a slight MBP increase. Using a swine experimental model similar to the above, Sundeman et al (1996) 6 have observed that 4.9% desflurane has not significantly changed hemodynamic responses to infrarenal aortic cross-clamping. However, 9.8% desflurane has decreased MBP and SVRI during crossclamping.…”
mentioning
confidence: 99%
“…Even so, with isoflurane in an intermediate concentration to those used by previous authors, there has been during aortic cross-clamping the same MBP behavior observed in the group receiving 0.7% isoflurane, that is, there was no impediment for a slight MBP increase. Using a swine experimental model similar to the above, Sundeman et al (1996) 6 have observed that 4.9% desflurane has not significantly changed hemodynamic responses to infrarenal aortic cross-clamping. However, 9.8% desflurane has decreased MBP and SVRI during crossclamping.…”
mentioning
confidence: 99%
“…Most of the experimental studies which have been previously conducted have produced controversial and inconclusive results. RBF has been found decreased 18 or unchanged 15,19 while an increase in RVR has usually been reported. 15,18,19 Many factors have been suggested to explain the discrepancies between the experimental studies, mainly anaesthesia management or species differences, but the method used to assess the renal perfusion may be accounted for too.…”
Section: Discussionmentioning
confidence: 92%
“…The blood flow effects of DES in the splanchnic region are the balanced net result of multiple, sometimes opposing, direct and indirect actions of the agent. Local vascular relaxation is expected (5), while decreases in perfusion pressure are likely to be produced by the negative inotropic cardiac effects of DES (6,8). In addition, effects mediated through autoregulation (9), baroreflex alterations and central nervous inhibition of sympathetic neurogenic vasoconstrictor discharge can concur.…”
Section: Discussionmentioning
confidence: 99%
“…To measure portal macrocirculatory flow, we used transit time ultrasound flowmetry. This technique is well established (6,18,20), non-traumatic to the vessel and measures blood flow quantitatively. For assessments of jejunal microcirculatory perfusion in the more superficial layers of the intestine, which to a major extent includes villi and mucosa, we used laser Doppler flowmetry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation